Students' preferred teaching approach for FAR150 / Mohamad Azmi Nias Ahmad, Syed Iskandar Zulkarnain Sayd Idris and Mohd Fazil Mohd Arif - Nias Ahmad, Moharnad Azmi; Sayd Idris, Syed Iskandar Zulkarnain; Mohd Arif, Mohd Fazil (2004)
The objectives of this paper are to study the students' preferred teaching approach for Financial Accounting 2 (FARI50) course, to examine relationship between students' perceptions towards the different teaching method and gender, and to examine relationship between student's perceptions towards the different teaching method with course status. It was found that the students perceive demonstrating the steps in solving problem, explaining in detail and giving clues as preferred teaching approach for FAR150. Further analysis conducted found that there is no relationship between students' perception towards the different teaching method among gender and there is no relationship between students perception towards the different teaching method with course status.